Actividades bucofaciales y el lenguaje oral en niños de 4 a 5 años de la escuela de educación básica Municipal Ecológica de la ciudad de Loja, periodo académico 2021-2022. - Palacios Azanza, Pamela Tatiana (2022)
Oral language is defined as an instrument of communication by which the child expresses his/her feelings, ideas or opinions, it helps the social relationship and it is of vital importance for the child’s cognitive, social and affective development; however, his/her growth will depend on the child’s age and the stimulation provided by the people around him or her. The purpose of this research was to support the incidence of orofacial activities to improve oral language in children from 4 to 5 years old at the Municipal Ecological basic education school of the city of Loja, academic period 2021-2022. This study had a quantitative to analyze, interpret, investigate and collect statistical data, besides, it is framed in a quasi-experimental design because it belongs to a non-random sample, similarly it is aligned in a descriptive scope, where the methods such as the inductive, deductive and the analytic-synthetic were used. Finally, in order to obtain initial and final results, the Navarre test of PLON-R was applied to 17 children of the Initial Level II, obtaining as a result that 16% were at normal level and after the intervention the percentage increases 19%, giving 35% at normal level; concluding that orofacial activities are exercises that stimulate the different organs involved in the speech of infants, gradually helping to strengthen all language skills so that the child can have a verbal fluency according to his/her chronological age for his school, family and social development. Key Words: Phonetics and phonology, stimulation, verbal fluency, Initial II, language skills, orofacial praxis.